2011
DOI: 10.3390/rs3010100
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Laser Scanning for the Site Type Identification of Mature Boreal Forest Stands

Abstract: Abstract:In Finland, forest site types are used to assess the need of silvicultural operations and the growth potential of the forests and, therefore, provide important inventory information. This study introduces airborne laser scanner (ALS) data and the k-NN classifier data analysis technique applicable to the site quality assessment of mature forests. Both the echo height and the intensity value percentiles of different echo types of ALS data were used in the analysis. The data are of 274 mature forest stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 31 publications
(36 reference statements)
1
21
0
Order By: Relevance
“…Selection of data and methods commonly used for mapping successional stages in boreal forests and other regions. Selected studies were found in both Alaskan (e.g., Epting and Verbyla [83] and Tanase et al [183]) and Eurasian (e.g., Vehmas et al [185] and Vehmas et al [184]) boreal regions. However, studies conducted in Eurasia are not specific to post-fire recovery sites.…”
Section: Monitoring Successional Stagesmentioning
confidence: 99%
See 4 more Smart Citations
“…Selection of data and methods commonly used for mapping successional stages in boreal forests and other regions. Selected studies were found in both Alaskan (e.g., Epting and Verbyla [83] and Tanase et al [183]) and Eurasian (e.g., Vehmas et al [185] and Vehmas et al [184]) boreal regions. However, studies conducted in Eurasia are not specific to post-fire recovery sites.…”
Section: Monitoring Successional Stagesmentioning
confidence: 99%
“…Combining field plots with remotely sensed data, however, provides an alternative approach for monitoring successional stages of forests across large spatial extents [177] (Table 6, [83,177,[181][182][183][184][185][186]). In boreal forest ecosystems, there are very few studies using optical sensors, such as Landsat TM/ETM+, to characterize post-fire patterns of succession [83,[187][188][189].…”
Section: Monitoring Successional Stagesmentioning
confidence: 99%
See 3 more Smart Citations